2023
DOI: 10.3390/plants12102021
|View full text |Cite
|
Sign up to set email alerts
|

Argentatin Content in Guayule Leaves (Parthenium argentatum A. Gray)

Abstract: Approximately one-third of the waste biomass from the cultivation of guayule (Parthenium argentatum A. Gray) for natural rubber production is leaf tissue; however, whether it can be valorized is not known. Guayulins and argentatins are potential high-value products that can be recovered from guayule resin during rubber/latex processing. Argentatins are highly abundant in guayule stem resin; however, unlike the guayulins, their occurrence in leaves has not been investigated. The present study determined the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For example, a study on maize plants found that optimal leaf excision from the top of the plants signi cantly improved biomass partitioning to seeds, resulting in higher seed yield [23]. Additionally, research on guayule plants suggested that the content of certain highvalue compounds in the leaves could be exploited, implying that broader leaves may not always directly correlate with higher biomass yields [24]. Furthermore, a study on beet leaves demonstrated that the recovery of bioactive compounds from the leaves could provide a sustainable solution for underutilized by-products, indicating that broader leaves do not necessarily translate to higher biomass utilization [25].…”
Section: Number Of Of Transplanted Pechaymentioning
confidence: 99%
“…For example, a study on maize plants found that optimal leaf excision from the top of the plants signi cantly improved biomass partitioning to seeds, resulting in higher seed yield [23]. Additionally, research on guayule plants suggested that the content of certain highvalue compounds in the leaves could be exploited, implying that broader leaves may not always directly correlate with higher biomass yields [24]. Furthermore, a study on beet leaves demonstrated that the recovery of bioactive compounds from the leaves could provide a sustainable solution for underutilized by-products, indicating that broader leaves do not necessarily translate to higher biomass utilization [25].…”
Section: Number Of Of Transplanted Pechaymentioning
confidence: 99%